Digoxin Induces Cardiac Hypertrophy Without Negative Effects on Cardiac Function and Physical Performance in Trained Normotensive Rats - Neves, Claodete Hasselstrom; Tibana, Ramires Alsamir; Prestes, Jonato; Voltarelli, Fabricio Azevedo; Aguiar, Andreo Fernando; Ferreira Mota, Gustavo Augusto; de Sousa, Sergio Luiz Borges; Leopoldo, Andre Soares; Leopoldo, Ana Paula Lima; Mueller, Andre; Aguiar, Danilo Henrique; Navalta, James Wilfred; Sugizaki, Mario Mateus (International Journal of Sports Medicine, 2017)
Cardiotonic drugs and exercise training promote cardiac inotropic effects, which may affect training-induced cardiac adaptations. This study investigated the effects of long-term administration of digoxin on heart structure and function, and physical performance of rats submitted to high-intensity interval training (HIIT). Male Wistar rats, 60 days old, were divided into control (C), digoxin (DIGO), trained (T), and trained with digoxin (TDIGO). Digoxin was administered by gavage (30 µg/kg/day) for 75 days. The HIIT program consisted of treadmill running 60 min/day (8 min at 80% of the maximum speed (MS) and 2 min at 20% of the MS), 5 days per week during 60 days. The main cardiac parameters were evaluated by echocardiograph and cardiomyocyte area was determined by histology. There were no group x time effects of digoxin, HIIT or interactions (digoxin and HIIT) on functional echocardiographic parameters (heart rate; ejection fraction) or in the maximum exercise test. There was a group x time interaction, as evidenced by observed cardiac hypertrophy in the TDIGO group evaluated by ratio of left ventricle weight to body weight (p<0.002) and cardiomyocyte area (p<0.000002). Long-term administration of digoxin promoted cardiac hypertrophy without affecting cardiac function and physical performance in rats submitted to HIIT.
Keywords: digoxin; high-intensity interval training; cardiac function; physical performance